A Story Told in a Whisper, or the Impossibility of Atonement - Sandra Regina Goulart Almeida (Ilha do Desterro)
This article analyzes the novel Sorry by the Australian writer Gail Jones in light of contemporary theories on decolonialism and the coloniality of power. It discusses how the novel addresses major issues that are central to an understanding of the Australian past and its history of colonization, exploitation of indigenous peoples and gendered subjects.